(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2025)
Background: Chronic kidney disease (CKD) substantially elevates the risk of cardiovascular complications, including peripheral arterial disease (PAD). However, the traditional method for PAD screening—the ankle-brachial index (ABI)—may be less effective in CKD patients due to vascular calcification, which can compromise the sensitivity of the test. Given this limitation, the study investigates femoral artery intima-media thickness (fIMT) as a potential early marker of atherosclerosis in individuals with CKD. Methods: A prospective observational study was conducted at Kempegowda Institute of Medical Sciences between April and September 2024. The study included 50 CKD patients under 50 years of age who underwent lower limb Doppler ultrasonography. Femoral artery intima-media thickness and the presence of plaques were assessed using a high-frequency ultrasound probe. The ABI was calculated for each patient, and renal function was evaluated using estimated glomerular filtration rate (eGFR). Additional clinical and demographic data including diabetes, hypertension, and smoking status were recorded. Results: Among the 50 participants, 18% showed increased femoral IMT, while 40% had detectable femoral artery plaques. The presence of plaques was more common in males, diabetics, hypertensives, and smokers. A significant positive correlation was observed between plaque formation and declining eGFR levels. Importantly, some patients with normal ABI values still demonstrated plaque presence on ultrasound, indicating that ABI alone may miss early or subclinical PAD in CKD populations. Conclusion: Femoral artery ultrasonography proved valuable in identifying early atherosclerotic changes in CKD patients, especially in cases where ABI results were within the normal range. These findings suggest that measuring fIMT and detecting plaques via ultrasound can serve as effective, non-invasive methods for early PAD detection in CKD, potentially enabling earlier intervention and improved cardiovascular risk management in this high-risk group.